AXA VALORICĂ A POEZIEI LUI DUMITRU MATCOVSCHI ŞI DREPTURILE DE AUTOR - FONARI, Conf. dr., Departamentul literatură română şi teorie literară, USM, Victoria (BIBLIOPOLIS, 2020)
The article is about the term „edge” in the creation of Dumitru Matcovschi. In the poetic text, Dumitru Matcovschi uses the word Mărgioară (edge) with the meaning „the country or the native land”. It is the space where he was, with people who have marked him. The poet makes the village on the banks of the Nistru – Vadul Raşcov – a myth of Mărgioară (edge): „The most beautiful./ No one in the book. /It was once here on ... / a mărgioară (an edge) / A shore waters / was once here about ...” (Tear of the Gods). Even if the word mărgioara will not always be written with a capital letter it is a cult accentuated by the force of a word that the common name becomes own. Status of the word Mărgioara amplifies the connotation of edges. From optical lexical, the edge is synonymous with marginal, peripheral, secondary ferrous, unimportant, watching etc. In this linguistic field the writer takes the position of Don Quixote and succeeds to make from something common knightly full of nobility accessories. Metamorphosis is determined by the aura that he makes out of the root word "edge". The achievement of the poet is like the king who has the power to gold, is the same enrichment not only materially but rather spiritual.